Adsorption of cadmium(ii) and copper(ii) from soil and water samples onto a magnetic organozeolite modified with 2-(3, 4-dihydroxyphenyl)-1, 3-dithiane using an artificial neural network and analysed by flame atomic absorption spectrometry1. Issue 14 (21st July 2015) - Shirani, Mahboube; Akbari, Ali; Hassani, Mohsen
<x xml:space="preserve">Abstract</x> A novel sorbent for the adsorption of cadmium and copper using an artificial neural network has been synthesised.